The genus Adicella McLachlan (Trichoptera, Leptoceridae) in Japan - Ito, Tomiko; Kuhara, Naotoshi; Katsuma, Nobuyuki (Zootaxa, 2013)
The Japanese species of the genus Adicella McLachlan (Trichoptera, Leptoceridae) are reviewed and confirmed, including a described species and 3 new species: A. makaria Malicky & Chantaramongkol 2002, originally described from Taiwan, A. trichotoma Ito & Kuhara sp. nov., A. paludicola Ito & Kuhara sp. nov., and A. strigillata Katsuma & Ito sp. nov. For clear comparisons, adults of all species are redescribed or described.